2013
DOI: 10.20525/ijrbs.v2i3.73
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting adoption of mobile banking in Pakistan

Abstract: In this research paper we investigated the determinants likely to influence the adoption of mobile banking services, with a special focus on under banked/unbanked low-income population of Pakistan. The adoption of mobile banking services has been a strategic goal, both for banks and telcos. For this purpose, Technology Acceptance Model (TAM) was used, with additional determinants of perceived risk and social influence. Data was collected by surveying 372 respondents from the two largest cities (Karachi and Hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
54
2
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(70 citation statements)
references
References 23 publications
8
54
2
6
Order By: Relevance
“…They found that household type, services, usage frequency, ease of use and uptake deter the use of mobile banking adoption of the financially excluded group. On the contrary, Kazi and Mannan (2013) identified innovative promotional and pricing strategies should adopt by the service providers to increase the number of acceptance. Findings of the researchers on the mobile banking adoption have been summarized in Table 1.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that household type, services, usage frequency, ease of use and uptake deter the use of mobile banking adoption of the financially excluded group. On the contrary, Kazi and Mannan (2013) identified innovative promotional and pricing strategies should adopt by the service providers to increase the number of acceptance. Findings of the researchers on the mobile banking adoption have been summarized in Table 1.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Till date, most of the research on mobile banking adoption (Aderonke, 2010;Akturan & Tezcan, 2012;Al-Jabri & Sohail, 2012;AlSoufi & Ali, 2014;Crabbe, Standing, Standing, & Karjaluoto, 2009;DiVanna, 2003;Goi, 2006;Gu, Lee, & Suh, 2009;Haig, 2002;Hanafizadeh, Behboudi, Abedini Koshksaray, & Jalilvand Shirkhani Tabar, 2014;Hassan, Rahman, Afrin, & Rabbany, 2014;Kabir, 2013;Karjaluoto, Koenig-Lewis, Palmer, & Moll, 2010;Karjaluoto, Riquelme, & Rios, 2010;Kazi & Mannan, 2013;Khraim, Al Shoubaki, & Khraim, 2011;Laforet & Li, 2005;Lee, Lee, & Kim, 2015;Luarn & Lin, 2005;Mattila, 2003;Mbiti & Weil, 2011;Medhi, Ratan, & Toyama, 2009;Nayak, Nath, & Goel;Oshunloye, 2009;Suoranta, 2003;Yu, 2012;Zhou, Lu, & Wang, 2010) either focus on developed countries or on developing countries from a narrow or urban scope. Most of the previous research is lagging behind in identifying the factors contributing to the adoption of mobile banking in rural areas.…”
Section: Introductionmentioning
confidence: 99%
“…Using the TAM, Kazi and Mannan (2013) have assessed the determinants of mobile banking adoption in the two largest cities of Pakistan (Karachi and Hyderabad) using a survey of 372 respondents, with particular emphasis on banked/unbanked population in the lowincome strata. The significant factors influencing adoption include: social influence, perceived usefulness, perceived risk and perceived ease-of-use, with the first (or social influence) being the significant positive determinant.…”
Section: Determinants Of Mobile Phone/bankingmentioning
confidence: 99%
“…(ii) The mobile banking literature has been based on survey data for the most part and focused on mobile banking adoption intensions (Gu et al, 2009 ;Medhi et al, 2009;Daud et al, 2011;Akturan & Tezcan, 2012 ;Kazi & Mannan, 2013;Alsheikh &Bojei, 2014 ;Cudjoe et al, 2015). We also complement this strand by using macroeconomic determinants classified into six main categories, consisting of 25 variables.…”
Section: Introductionmentioning
confidence: 99%
“…mainstream survey-based, country-specific and microeconomic studies (Kazi & Mannan, 2013;Alsheikh & Bojei, 2014;Cudjoe et al, 2015).…”
Section: Introductionmentioning
confidence: 99%